Pengaruh Latihan Koordinasi Mata Tangan dan Kekuatan Otot Lengan Terhadap Akurasi Lemparan Bola Petanque (Indonesian Journal for Physical Education and Sport, 2021)
Dias Ayu Asmarani SN. 2020. The influence of hands and eyes coordination, arm muscle strength towards the petanque ball throwing accuracy. Final Project, Physical Education, Health and Recreation, Science Sport Faculty, Semarang State University. Supervisor: Ipang Setiawan, S.Pd., M.Pd. Keywords: The Influence of Hands and Eyes Coordination Exercise, Arm Muscle Strength, Junior High School Students. The needed aspects in petanque are concentration, feeling and accuracy. Further more the good coordination between hands eyes and arm muscle strength will improve the accuracy of petanque ball throwing. There are some exercise must be done to improve the accuracy of the players throwing. The coordinating of hands and eyes exercise is very important to control the direction of our throwing to hit the target punetually and the exercise of arm muscle strength in throwing boule needs good and strong arm muscle. Based on the previous explanation, we can conclude that problem should be researthed is the influence of hands and eyes coordination and the strength of arm muscle towards the boule throwing accuracy. The methode of this research is experimental method with the subject the students of extracurricular of Junior High Scholl 1 Jatibarang. Using total sampling data of pree-test pointing petanque and post-test pointing petanque. After pree-test exercise of hands and eyes coordination were given to experiment group 1 and the strength of arm muscle exercise for experiment group 2, while the control group was not trained. Then the data was analized using spss quantitative software. The average scores of the pree-test result 9,6 for experiment group 1, 9,8 for the experiment group 2, and 10,1 for the control group. After the treatment, the experimet group 1 got 15,8 , the experiment group 2 got 14,5 while the control group got 10,8. The conclution of the research is that experiment group 1 got the most significant improvement up to 64,58% , the experiment group 2 is 46,94% while the control group improved less significant that is 6,93%.